11 - Generational Variations in Purpose of Childbearing among Ever-Married Women and Implications for Contraceptive Behaviour in Idanre Town Ondo State - Wusu, Onipede (African Sociological Review, 2022)
Demographic literature is abundant on the factors accountable for rapid population growth in Nigeria. However, knowledge about the likely implicit changes in the demographic imaginations of women in Nigeria is scanty. Hence, this study employed a qualitative methodology to explore the generational variations in the purpose of childbearing and implications for contraception among ever-married women within the social exchange framework in Idanre Town. The objective was to examine the implicit changes taking place in the demographic imagination of rural women by comparing three generations of women. The research team conducted 25 in-depth interviews (IDI) among purposively sampled ever-married women in April 2019. The data were content analysed. The analysis suggests that the purpose of childbearing varied across the three generations. The younger generation was less likely to indicate the desire to depend on children for their future survival compared to the middle and older generations. As a result, younger generation women would embrace contraceptives more than the other generations. Therefore, the exploration undertaken here suggests that the demographic imagination of the younger generation of women in the Town was undergoing implicit and noticeable changes that may continue to promote modern contraception in the population. Policies to facilitate female education and employment must continue to be the focus of policymakers in order to drive sustainable elevation of modern reproductive behaviour in Nigeria, especially in rural areas.